An Investigation Into Vietnamese And English Speech Sounds Pronounced By High School Students In Ly Son Island, Quang Ngai Province - Trần Nguyễn Thùy Dương (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study has been conducted basing on the contrastive analysis between the sound systems of English and Vietnamese Ly Son dialect in order to find out the influence of the dialect on Ly Son students’ pronunciation of English sounds. The study has focused on investigating students’ performance of eight English sounds including six vowels [] [] [] [] [] [] and two consonants [] [] in isolated words and sentences which all were recorded, described, reckoned up and analyzed. The combination of three research methods: descriptive method; quantitative method and contrastive analytic methods was used flexibly. Questionnaire and recording were used to collect the data. The study concludes that [] and [] are two simplest sounds to Ly Son students, meanwhile [] and [] and [] are the most difficult ones. Some solutions were proposed in order to improve teaching and learning English pronunciation at Ly Son High School.